2017
DOI: 10.1002/2016gc006569
|View full text |Cite
|
Sign up to set email alerts
|

A geochemical and geophysical reappraisal to the significance of the recent unrest at Campi Flegrei caldera (Southern Italy)

Abstract: Volcanic unrest at calderas involves complex interaction between magma, hydrothermal fluids, and crustal stress and strain. Campi Flegrei caldera (CFc), located in the Naples (Italy) area and characterized by the highest volcanic risk on Earth for the extreme urbanization, undergoes unrest phenomena involving several meters of uplift and intense shallow microseismicity since several decades. Despite unrest episodes display in the last decade only moderate ground deformation and seismicity, current interpretati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 89 publications
(304 reference statements)
2
71
0
Order By: Relevance
“…In this case, deep drilling provides the best mean to obtain direct information on processes occurring at depth and represents a key tool for reconstructing the caldera structure and understanding the volcano dynamic and volcanic risk assessment [10]. The highly urbanised Campi Flegrei Caldera have been experiencing decades of unrest, with uplift rates up to 1 m/y, thousands of microearthquakes per year [11] and strong geochemical anomalies [12], leading to people evacuation of Pozzuoli town in [1982][1983]. At the present, the alert level for the caldera has been moved from 'base' (ordinary activity of volcano) to 'attention' status.…”
Section: Introductionsupporting
confidence: 69%
“…In this case, deep drilling provides the best mean to obtain direct information on processes occurring at depth and represents a key tool for reconstructing the caldera structure and understanding the volcano dynamic and volcanic risk assessment [10]. The highly urbanised Campi Flegrei Caldera have been experiencing decades of unrest, with uplift rates up to 1 m/y, thousands of microearthquakes per year [11] and strong geochemical anomalies [12], leading to people evacuation of Pozzuoli town in [1982][1983]. At the present, the alert level for the caldera has been moved from 'base' (ordinary activity of volcano) to 'attention' status.…”
Section: Introductionsupporting
confidence: 69%
“…The aforesaid could justify the discrepancy recently highlighted by Moretti et al (2017) between weak geophysical signals (moderate uplift and low seismicity) and drastic changes in geochemical indicators characterizing the present stage of the CF history.…”
Section: Discussionmentioning
confidence: 99%
“…As all calderas, CF represents a complicated makeup that includes a magmatic plumbing system with a depth of up to ∼ 8 km (Bodnar et al, 2007;Zollo et al, 2008;Vitale et al 2014;Moretti et al, 2017), feeding the overlying hydrothermal system (Chiodini et al, 2010;Troiano et al, 2011;De Siena et al, 2017a) through an intricate network of fractures (Zollo et al, 2008;De Siena et al, 2010;Byrdina et al, 2014). A clear picture of the feeding mechanisms and its dynamics is one of the central open questions regarding CF and is subject to ongoing debate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[]; (b) picture of fumarole emissions at Solfatara, analyzed by Moretti et al . []; the ratio between H 2 O and CO 2 , determined in the last 34 years by these authors, is shown; (c) picture of the Roman Market (Macellum) in Pozzuoli town, with the marble columns of the “Serapis” Temple which, with their bores (caused by molluscs) indicating the marine ingression levels during the time, allowed to reconstruct the secular variations of the ground level since Roman times (shown in this frame, from Bellucci et al , ); (d) picture of the tuff cliff of Rione Terra, at the center of Pozzuoli town and the Port; this is the site of maximum measured deformation at Campi Flegrei, whose trend since 1905 to present is shown below the picture, as measured by precision levellings until 2000 and by continuous GPS after this date; (e) picture of the dismissed steel factory of Bagnoli (ILVA), which hosted the drilling site CFDDP; on the right side, the stratigraphic sequence recovered in the well is shown with recovered ages and depths of main samplings (red stars). (Figures and composition by Claudio Serio, photos by Alessandro Fedele).…”
Section: Understanding and Mitigating Volcanic Risk: The Case Of Campmentioning
confidence: 99%